Two new species of the enigmatic genus Stenophareus (Opiliones: Laniatores: Stygnidae) from the Venezuelan Guiana Shield - Manzanilla, Osvaldo Villarreal; Donascimiento, Carlos; Rodríguez, Carlos J. (Zootaxa, 2007)
Two new species of Stenophareus are described from the Guiana Shield region of Venezuela. S. aonda sp. n. (type-locality: Auyán-tepui, Bolívar) is characterized by ocular and tegumentary depigmentation and by extreme pedipalp and leg elongation, representing the first troglomorph stygnid. S. guerreroi sp. n. (type-locality: Chimantá-tepui, Bolívar) is distinguished by a swollen proximal-most tarsomere of leg I and by the presence of an anterior tubercle on the anal opercle. Putative phylogenetic affinities of the genus Stenophareus within the Stygninae are discussed.Se describen dos especies nuevas del género Stenophareus provenientes de la región del escudo guayanés de Venezuela. S. aonda sp. n. (localidad tipo: Auyán-tepui, Bolívar) es caracterizado por depigmentación ocular y del tegumento y pedipalpo y patas extremadamente largos, representando el primer estígnido troglomorfo. S. guerreroi sp. n. (localidad tipo: Chimantá-tepui, Bolívar) es diagnosticado por el engrosamiento del tarsómero más proximal de la pata I y presencia de un tubérculo anterior en el opérculo anal. Las afinidades filogenéticas putativas del género Stenophareus dentro de la subfamilia Stygninae son discutidas.